2010
DOI: 10.1007/s12144-010-9091-9
|View full text |Cite
|
Sign up to set email alerts
|

Paranormal Encounters as Eyewitness Phenomena: Psychological Determinants of Atypical Perceptual Interpretations

Abstract: Many people who report paranormal sightings (e.g., Bigfoot and UFO aliens) are apparently sincere. This places many such sightings in the category of eyewitness errors, rather than of deliberate deception. Recent research has supported this idea; in an earlier paper, we demonstrated that paranormal beliefs are facilitated by tendencies toward attention deficit hyperactive disorder, dissociation, and depression. These characteristics predicted specific patterns of beliefs in several paranormal phenomena. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Similarly, people who report being abducted by aliens score high on tests of fantasy proneness, psychological absorption and childhood imaginings, and introversion (Parnell 1988;Parnell and Sprinkle 1990;Swami et al 2011). Sharps et al (2010) also found that increased paranormal belief was associated with increased dissociative thinking (lower analytical or fact-based thinking processes and higher intuitive or gestalt thinking). Specifically, with respect to subcategories of the revised paranormal belief scale, dissociation was correlated with belief in bigfoot, aliens, and ghosts.…”
Section: Student's Propensity For Beliefmentioning
confidence: 98%
“…Similarly, people who report being abducted by aliens score high on tests of fantasy proneness, psychological absorption and childhood imaginings, and introversion (Parnell 1988;Parnell and Sprinkle 1990;Swami et al 2011). Sharps et al (2010) also found that increased paranormal belief was associated with increased dissociative thinking (lower analytical or fact-based thinking processes and higher intuitive or gestalt thinking). Specifically, with respect to subcategories of the revised paranormal belief scale, dissociation was correlated with belief in bigfoot, aliens, and ghosts.…”
Section: Student's Propensity For Beliefmentioning
confidence: 98%
“…While the Doris Bither case was extreme and sensational, its phenomenology underscores why the relation between paranormal ideations and psychological wellness or symptom perception is an important and burgeoning area of study (e.g., Dein, 2012;Mathijsen, 2016;Rabeyron & Loose, 2015;Sar, Alioğlu, & Akyüz, 2014;Sharps et al, 2010;Simmonds-Moore, 2012). We even argue that research increasingly suggests the possibility of a Haunted People Syndrome (HP-S) 1a moniker proposed here that was inspired by the title of an early parapsychological book by Carrington and Fodor (1951).…”
Section: Introductionmentioning
confidence: 79%